BACH2 in TRegs Limits the Number of Adipose Tissue Regulatory T Cells and Restrains Type 2 Immunity to Fungal Allergens - Amanda Contreras; Darin L. Wiesner; Brock Kingstad-Bakke; Woojong Lee; John P. Svaren; Bruce S. Klein; M. Suresh (Journal of Immunology Research)
FoxP3+ regulatory T cells (Tregs) are essential for self-tolerance and moderating tissue-damaging inflammation. Tregs that develop and mature in the thymus are classified as central Tregs or effector Tregs based on whether Tregs predominately inhabit secondary lymphoid organs (central Tregs) or tissues (effector Tregs). By generating mice that are conditionally deficient for Bach2 in peripheral Tregs, we have examined the role of Bach2 in regulating Treg homeostasis and effector functions. Unlike global and T cell-specific Bach2-deficient mice, Treg-specific Bach2 ablation did not result in unprovoked TH2 inflammation in the lungs. However, Bach2 deficiency in Tregs led to augmented expressions of IRF4, BATF, and GATA3 and a significant increase in the accumulation of ST2 (IL-33R)+ve effector Tregs in the spleen and visceral adipose tissue (VAT) but not in the lungs. Enhanced Bach2-deficient Treg numbers in VAT was not linked to hyperresponsiveness to exogenous IL-33 in vivo. Most strikingly, Treg-specific Bach2 deficiency resulted in enhanced fungal protease-induced Type 2 allergic inflammation in the lungs, with no detectable effects on Type 1 responses to systemic or respiratory viral infections. In summary, we ascribe vital roles for Bach2 in peripheral Tregs: as a transcriptional checkpoint to limit precocious differentiation into effector Tregs in lymphoid tissues and as a regulator of the functional program that restrains Type 2 but not Type 1 inflammation in lungs. Results presented in this manuscript implicate dysregulated Tregs in the pathogenesis of airway hypersensitivities, asthma, and other allergic disorders.